Closely related strains of Bradyrhizobium contained in commercial inoculates of soybean are identified by a set of PCR reactions - López, Silvina (2012)
The aim of this work was to identify closely related rhizobia, used to formulate commercial inoculants, using polymerase chain reaction (PCR). Repetitive extra-genic palindromic (REP) and BOX fingerprints hardly discriminate among a set of commercial strains. PCR targeted at repetitive RSα successfully allow discriminating within representatives of Bradyrhizobium. These fingerprints clustered isolates at a higher level of similarity and proved to be an important tool to complement the information provided by the other markers. The results suggest that mutants occur along the bacterial culture, during inoculant production. However, independently of the number of amplification reactions used to characterize and identify organisms, mispriming always generates artifactual diversity. In addition to this, it seems that combining reactions such as BOX or REP fingerprinting with reactions targeted at the RSα sequence, generates a more reliable identification tool to characterize closely related bradyrhizobia.